Development of Local Wisdom-Based Learning Modules and Teacher Training for Character Strengthening - Wajnah, Wajnah; Suwarma, Dina Mayadiana; Wahdah, Wahdah; Jumriah, Jumriah; Husain, Husriani (PT Inovasi Pratama Internasional, 2025)
Character education remains a pivotal concern in contemporary Indonesian educational contexts, particularly in preserving cultural values amid globalization while fostering moral development in students. This research addresses the urgent need for contextually relevant pedagogical approaches by developing and implementing learning modules based on local wisdom (kearifan lokal) integrated with comprehensive teacher training programs. Employing qualitative methodology through thematic analysis of interview data, observational records, and documentary evidence collected from eight teachers across diverse school settings in Indonesia, this study examines the effectiveness of locally-contextualized learning modules in strengthening character education. The findings reveal that 93.75% of teachers perceived the modules as highly useful, with student character development indicators demonstrating improvements ranging from 29% to 33% across six key character values within a four-month implementation period. Community stakeholder engagement, particularly involving local elders (90% participation) and religious leaders (88% participation), emerged as a crucial supporting factor in implementation success. This research demonstrates that integrating indigenous knowledge with pedagogical training creates sustainable frameworks for character education that honor cultural identity while achieving educational objectives. The results have significant implications for educational policy, teacher professional development, and the preservation of cultural heritage through formal education systems..